VD_FINDINFO AP / 2011 / 39 vom 20. Dezember 2010 - VD Tribunal cantonal (2010)
FIXATION DE LA PEINE, ACTE D'ORDRE SEXUEL SUR UN INCAPABLE DE DISCERNEMENT | 191 CP, 47 CP, 411 let. h CPP, 411 let. i CPP